The Concept of Locally Contained Independent Learning Model: Glocalization in Elementary School Indonesian Language Learning in the Coastal Area of Southwest Papua - Teguh Yuliandri Putra; Vismaia Sabariah Damaianti; Yeti Mulyati; Andoyo Sastromihardjo (Universitas Cokroaminoto Palopo, 2025)
This study describes the concept of an independent learning model as a demand for 21st century learning that is aligned with local wisdom content. Through the concept of glocalization in learning, it will be able to increase the cognitive potential of students more optimally. This study aims to help improve the quality of learning to read and write for elementary school students in grade 1 in remote coastal areas of Southwest Papua. This study uses a descriptive qualitative method to present in a structured manner the concept of an independent learning model with local content in learning Indonesian (beginning reading and writing). Data collection techniques and instruments in this study use observation, interview, and documentation techniques. The results of this study are 1) a description of the syntax concept of an independent learning model with local content; 2) a description of the stages of glocalization of Indonesian language learning; and 3) a description of the value of student learning outcomes. The conclusion of this study is that through glocalization of Indonesian language learning in elementary school children, it will be able to improve the ability to read and write very effectively through five syntax models of independent learning with local wisdom content.